TINJAUAN KRITIS TERHADAP PENDIDIKAN AGAMA MULTIKULTURAL BARBARA WILKERSON - Slamet Santoso (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2018)
This article deals with the thought of Barbara Wilkerson that discusses the religious education in the context of the multiple culture. The writer argues that Wilkerson’s theory can give contribution to develop the religious education of the multiple culture in Indonesian context. It is important to be noted that Wilkerson does not answer directly to the problems of the multiple culture in Indonesia context. The writer also discusses critically Wilkerson’s theory, especially when such a theory is applied in Indonesian context.